Romantic Sadness in the Themes and Genres of Popular Minang Songs: A Producer's Perspective - Arief Jintan Permata; Asril Asril (Melayu Arts and Performance Journal, 2025)
The research titled â€œRomantic Sadness in the Themes and Genres of Popular Minang Songs: A Producerâ€™s Perspectiveâ€ uses a semiotic analysis approach. Its aim is to uncover various symbols, metaphors, and hidden meanings that depict feelings of loss, longing, and disappointment, particularly in the context of romantic relationships. This research employs a qualitative method with a descriptive approach, considered the most suitable for addressing the raised issues. The study is supported by theories focused on analyzing the production process and texts in popular Minang songs. Data is collected through literature studies on Minangkabau music, as well as direct observations from digital media where these songs were released. The results of the study show that romantic sadness, which frequently appears in popular Minang songs, has a profound impact on the social and cultural life of the community. These songs not only influence the way society perceives love, relationships, and loss, but also play an essential role in strengthening Minangkabau cultural identity and social values. Thus, this research provides new insights into how Minang songs with themes of romantic sadness reflect the beauty and complexity of emotions while preserving the Minangkabau culture.